Application value of the vertical and horizontal hierarchical responsibility management nursing model in patients undergoing appendectomy - Miao, Jingjing; Zhang, Qianqian; Li, Huimin (Frontiers in Surgery, 2025)
BackgroundAppendicitis is a common acute abdominal disease with characteristic symptoms. The vertical and horizontal hierarchical responsibility management nursing model strengthens nursing staff training, refines nursing work contents, and contributes to improved patient care during hospitalization.ObjectiveThis study aimed to evaluate the application value of the vertical and horizontal hierarchical responsibility management nursing model in patients undergoing appendectomy.MethodsA total of 86 acute appendicitis patients undergoing appendectomy in our hospital from January 2021 to January 2023 were selected as research subjects. All patients were assigned to a responsibility group and a control group using the random number table method, with 43 patients in each group. The control group underwent routine nursing intervention, whereas the responsibility group underwent management and nursing with a vertical and horizontal hierarchical responsibility system.ResultsFirst postoperative mealtime, first postoperative exhaust time, postoperative hospitalization time, and first postoperative out-of-bed activity time in the responsibility group depicted depletion relative to those of the control group (p < 0.05). The total nursing satisfaction rate in the responsibility group depicted an elevation relative to that in the control group post-nursing care (p < 0.05). The incidence of complications in the responsibility group 14 days post-surgery depicted depletion relative to that in the control group (p < 0.05). The QOL scores in both groups post-nursing care depicted elevation relative to before, and the responsibility group depicted elevation relative to that in the control group (p < 0.05).ConclusionThe application of the vertical and horizontal hierarchical responsibility management nursing model in appendectomy patients can improve clinical nursing efficacy and facilitate patient recovery, which is worthy of clinical application.